Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.17265/1934-7359/2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Recycled Coarse Aggregate in Concrete Mixes

Abstract: In this paper, the effect of the source of recycled coarse aggregate on the properties of concrete is investigated. The tests were conducted on concrete made from three sources of recycled aggregates: (1) old concrete with unknown strength, (2) old concrete with a known compressive strength of 21 MPa, and (3) old concrete with a known strength of 42 MPa. The three sources of recycled aggregates were used to produce new concrete with a target compressive strength of 21 MPa. The first and third sources of recycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The experimental test results demonstrate that the tensile strength of pervious concrete drops from 1.56 MPa when natural aggregate is used to 0.67 MPa when recycled aggregate is used. Although concrete employing recycled aggregate is expected to be weaker in tension when compared with concrete containing natural aggregate, the observed drop is much more drastic when compared with previous studies by the authors [56][57][58][59][60][61] on non-pervious concrete. The inferior quality of the recycled coarse aggregate due to its higher water absorption, lower density, possible content of organic substances, higher level of crushability, and reduced abrasion resistance contributes to lower tensile strength of pervious concrete.…”
Section: Split Tensile Strengthcontrasting
confidence: 56%
See 1 more Smart Citation
“…The experimental test results demonstrate that the tensile strength of pervious concrete drops from 1.56 MPa when natural aggregate is used to 0.67 MPa when recycled aggregate is used. Although concrete employing recycled aggregate is expected to be weaker in tension when compared with concrete containing natural aggregate, the observed drop is much more drastic when compared with previous studies by the authors [56][57][58][59][60][61] on non-pervious concrete. The inferior quality of the recycled coarse aggregate due to its higher water absorption, lower density, possible content of organic substances, higher level of crushability, and reduced abrasion resistance contributes to lower tensile strength of pervious concrete.…”
Section: Split Tensile Strengthcontrasting
confidence: 56%
“…The tests showed that 100% replacement of the aggregate caused the compressive strength of pervious concrete to reduce by 36%, from 7.08 to 4.53 MPa. Earlier studies by the first two authors [56][57][58][59][60][61] on non-pervious concrete have indicated the full replacement of natural coarse aggregate with recycled aggregate from construction demolition waste obtained from the same source can reduce the compressive strength by an average of just 10-15%. The lack of adequate amount of fine aggregate in pervious concrete increases the importance of the coarse aggregates and the bond between them to the mechanical properties of the concrete.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…However, concerns about variability of recycled aggregate (RA) properties have limited the use of RCA in structural applications. Several research efforts were devoted to evaluating fresh and hardened concrete properties containing different percentages of coarse recycled aggregate [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. However, research conducted on the structural behavior of RCA is limited and often contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Some other studies [10,11] concluded that the use of admixtures or silica fume can improve the concrete strength, when using recycled aggregates. The concrete strength, after using admixtures, showed values that are very close to those of the concrete made with natural aggregates.…”
Section: B Properties Of Concrete Produced By Recycled Aggregatesmentioning
confidence: 99%